Present Situation of Pressure Flooding Technology for Injection Enhancement in Low Permeability Reservoirs - Huang, Jiaxi; He, Ruijun; Shen, Tao (International Journal of Electric Power and Energy Studies, 2025)
Low permeability reservoir generally exists low permeability, small pore pressure, high start-up pressure gradient and difficult injection. Energy injection technology for low permeability reservoir is always concerned by people. Based on the difficulty of "no injection, no production" in low permeability reservoir, pressure drive water injection technology is put forward. This paper introduces pressure drive technology according to literature investigation and current situation of pressure drive technology at home and abroad.